Information content as a parameter of acoustical hologram reconstructibillty - KALUŽNÝ, Jan; ZIELENIUK, Jerzy K. (Archives of Acoustics, 1981)
The aim of this paper is to discuss the information content of an acousticalhologram and to determine its dependence on the determining parameters. It is also to look for the threshold of the information content which has to be reached in order to perform a successful reconstruction of the hologram.